Dampak Pasar Karbon Terhadap Keuangan Perusahaan Dalam Konteks Kebijakan Lingkungan (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
Carbon markets have become a key instrument in global efforts to reduce greenhouse gas (GHG) emissions and address the impacts of climate change. By implementing mechanisms such as cap and trade and carbon taxes, carbon market policies create economic incentives for companies to reduce their emissions efficiently. This research adopts a qualitative approach with a focus on case studies of several companies in various environmental policy contexts. Through in-depth interviews with key decision makers and analysis of internal documents, this research explores how carbon markets influence companies' long-term financial strategies. The results show that companies are responding to carbon markets by adopting strategies of investing in green technologies, product diversification, and operational adjustments to comply with stringent regulations. While carbon markets provide incentives for innovation and sustainability, they also introduce financial challenges such as the cost of owning carbon permits and potential increases in energy prices. Careful management of these risks and opportunities is crucial to ensure operational sustainability and company growth amidst increasingly complex global market dynamics. This study not only fills a gap in the literature on environmental economics, but also provides guidance for practitioners and policy makers in designing sustainability solutions effective in the future.
Keywords: Environmental Policy; Corporate Finance; Carbon Market